Four-point bending cycling: The alternative for thermal cycling solder fatigue testing of electronic components. (July 2017) - Vandevelde, Bart; Vanhee, Filip; Pissoort, Davy; Degrendele, Lieven; De Baets, Johan; Allaert, Bart; Lauwaert, Ralph; Zanon, Franco; Labie, Riet; Willems, Geert
Abstract: This paper deals with an alternative testing approach for quantifying the life time of board level solder joint reliability of components. This approach consists of applying a relative shear displacement between component and Printed Circuit Board (PCB) through cyclic board bending. During the cycling, the temperature is kept constant, preferably at elevated temperature in order to accelerate the creep deformation of the solder joint. This is done in a four-point bending setup which allows to apply an equal loading on all components lying between the inner bars. The scope of the paper is, firstly, to evaluate if the four point bending testing generates the same fatigue fracture as in thermal cycling; secondly, that the measured life times can be also predicted through finite element simulations; and thirdly if the technique can finally accelerate the cycling frequency to reduce the testing time. Highlights: 4pt bending experiments on test boards with 24 soldered daisy chain WL-CSP's. Benchmarking these results with thermal cycling, we made following conclusions: The same failure mode is generated, namely solder joint fatigue fractures. The joints fails faster with 4pt bending for a similar applied relative shear displacement. With 4-pt bending cycling, the test time could be reduced by a factor of three.